1996
DOI: 10.1093/oxfordjournals.deafed.a014294
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Information-processing Capabilities and Cochlear Implants: Implications for Preoperative Predictors of Speech Understanding

Abstract: In this study, we examined preoperative verbal cognitive capacity in 11 deafened adults who were cochlear implant candidates and reexamined level of speech understanding after 6-8 months' experience with the implant. Verbal cognitive performance in the implant group was compared in a group of normal hearing subjects and in nonimplanted group of deafened adults. The three groups performed on par with each other with an exception: The individuals in the cochlear implant group and the nonimplanted group of deafen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 17 publications
7
65
4
Order By: Relevance
“…It has been reported, however, that a visual monitoring task that requires rapid processing of sequential signals is related to spoken word recognition [Gantz et al, 1993;Knutson et al, 1991]. In addition, Lyxell et al [1996] found that processing speed and WM measured prior to surgery predicted speech recognition ability after implantation, and Kropp et al [2000] reported that general intellectual capacity, visual memory and nonverbal reasoning in adult CI recipients were correlated with the ability to perceive spoken numbers but not open-set words or sentences. Thus, the evidence to date from behavioral research concerning which cognitive abilities affect CI outcome in adult recipients is mixed, and it is as yet unclear whether just a few basic, domain-specific cognitive functions are important or whether individual differences in general intellectual ability underlie the variability in outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported, however, that a visual monitoring task that requires rapid processing of sequential signals is related to spoken word recognition [Gantz et al, 1993;Knutson et al, 1991]. In addition, Lyxell et al [1996] found that processing speed and WM measured prior to surgery predicted speech recognition ability after implantation, and Kropp et al [2000] reported that general intellectual capacity, visual memory and nonverbal reasoning in adult CI recipients were correlated with the ability to perceive spoken numbers but not open-set words or sentences. Thus, the evidence to date from behavioral research concerning which cognitive abilities affect CI outcome in adult recipients is mixed, and it is as yet unclear whether just a few basic, domain-specific cognitive functions are important or whether individual differences in general intellectual ability underlie the variability in outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, relatively little other research has focused directly on auditory working memory in users of cochlear implants. Lyxell, Andersson, Arlinger, Bredberg, Harder, and Ronnberg (1996) have, however, examined in adult cochlear implant users whether it might be "possible to predict the level of speech understanding (postimplant) by means of a preoperative cognitive assessment." Because Lyxell had previously obtained results suggesting that individual differences in processing speed and working memory capacity could account for a portion of the variability found in the speechreading/lipreading scores of normal-hearing adults, he hypothesized that this same relationship might also be observed in users of cochlear implants.…”
mentioning
confidence: 99%
“…The task is to correctly identify the pairs of antonyms among the five words of each item in five minutes. The test has been used repeatedly for the purpose of estimating level of verbal ability in participants in different projects (Lyxell et al, 1996;.…”
Section: Verbal Abilitymentioning
confidence: 99%
“…The test has been developed by Lyxell et al (1996) in accordance with cognitive theories on phonological processing. The task was to identify the pairs of words that rhymed, regardless of how the words were spelled or what font size was used.…”
Section: Phonological Skills and Phonological Working Memorymentioning
confidence: 99%
See 1 more Smart Citation